Distribution of endocrine-disrupting chemicals in colloidal and soluble phases in municipal secondary effluents and their removal by different advanced treatment processes. (March 2019) - Huang, Yu; Li, Wentao; Qin, Long; Xie, Xianchuan; Gao, Bin; Sun, Jie; Li, Aimin
Abstract: In this work, the partition of endocrine-disrupting chemicals (EDCs) in colloid-bound and truly dissolved phases in municipal wastewater before and after advanced treatment processes was determined. The effluents, which were filtered using a 0.45 μm membrane, were further separated with the 1 kDa cross-flow ultrafiltration system into two phases, namely, colloidal phase (0.45 μm-1 kDa) and soluble phase (<1 kDa), and the partition coefficients of typical EDCs to colloids (Kcoc) were calculated. The removal of typical EDCs and their estrogenic activity in secondary effluent by coagulation sedimentation (CS), granular activated carbon (GAC) adsorption, magnetic ion exchange resin (NDMP), and ozone processes was compared. Results show that the percentages of colloid-bound EDCs were noteworthy and ranged between 7.8% and 44.3% in secondary effluents. The reduction in EDCs resulting from the GAC adsorption process was positively correlated to their logKcoc, thus suggesting that the adsorption of EDCs onto granular activated carbon and colloids exhibited a similar phenomenal character. Ozone oxidation was most effective in removing both colloidal phase and soluble phase EDCs, whereas CS displayed a relatively adequate performance in reducing colloidal EDCs. EDCs with lower Kow values exhibited higher removal by ion exchange resin. The combination of modified NDMP and ozonation processes achieved the best performance in reducing estrogenic activity and satisfying the predicted no-effect concentration (PNEC). Graphical abstract: Image 1 Highlights: Colloid-bound EDCs ranged between 7.8% and 44.3% in secondary effluents. Coagulation showed better performance in the removal of colloid-bound EDCs than soluble ones. Removal of EDCs by the activated carbon had positive correlation with their logKcoc. The ozonation achieved the best EDC removal, whereas the NDMP showed the highest EEQ reduction. The effluent treated by the combined NDMP and ozonation reached PNEC.